Podcast as Disaster Mitigation Information Media on BNPBÔÇÖs Youtube Account - Susanti, Susi; Burhanuddin, Nunu; Azmi, Novia Amirah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
BNPB podcasts still face challenges in attracting the interest of the wider community, such as the low number of enthusiasts in BNPB podcasts resulting in a lack of public awareness of environmental issues. This study aims to analyze the effectiveness of disaster mitigation messages delivered through the BNPB podcast and identify the obstacles faced by BNPB in disaster mitigation counseling through the BNPB Podcast. This research uses a qualitative method with content analysis based on Everett Rogers' innovation diffusion theory, which includes innovation, social system, information dissemination, and timeframe. The data analyzed is podcast content from the BNPB_Indonesia YouTube account throughout. The aim was to identify the types, messages conveyed and BNPB's communication strategy. Public participation was evaluated through observational data, such as the number of likes and comments. Based on the results of the study, it can be concluded that BNPB podcasts include innovating mitigation messages, strengthening social systems, disseminating information, community response, follow-up to BNPB podcasts and obstacles faced in these podcasts. BNPB through the podcast innovated disaster preparedness and handling messages, and introduced Inarisk web technology to support it. Despite the potential for wide reach, the podcast content lacks audience interest, resulting in a minimal number of listeners. to be more effective, BNPB needs to strengthen promotion and interaction with listeners.